Risk assessment of logistic activities in foreign economic activity as a component of efficient management by a pharmaceutical company - Zaharko, Natalia; Sahaidak-Nikitiuk, Rita; Demchenko, Natalia (ScienceRise: Pharmaceutical Science, 2019)
Aim. The aim of the study is to develop a methodology for assessing the level of risk of the logistic component of foreign economic activity (FEA) of the pharmaceutical company (PhCo). Materials and methods. The study used methods of synthesis, analysis and synthesis, content analysis. To determine the risks of logistics in the foreign trade of pharmaceutical companies, an expert survey method was used. The survey was attended by leading specialists of departments of PhCo, whose functional responsibilities are related to the implementation of FEA. The total number of experts was 50 people. 100 % of respondents have a higher education, they are divided into the work experience: 0-10 years - 11 %, 11-20 years - 27 %, 21-25 years - 53 %, over 25 years - 8 %. According to the gender, 83 % of women and 17 % of men participated in the survey. Experts’ conclusions are grounded. Results. It is determined that under the risk of logistics in the field of foreign trade of pharmaceutical companies it is appropriate to understand the likelihood of occurrence of events in the field of foreign trade of PhCo in relation to the management of all types of flows when they pass through the country’s borders, which leads to certain consequences in space and time, namely, loss of part of the company’s income, foreign partners, delays in fulfilling obligations to other partners in the untimely delivery of active pharmaceutical ingredients (API), fines, penalties, etc. It is proved that the risks of logistic activity in the field of foreign economic activity on the basis of the species include the following subspecies: the risk of partnership, information, transport, innovation, organization, procurement of imported API, main and auxiliary materials, sale (export) of finished medicines, storage and loss of profit. Conclusions. The conducted research has led to the conclusion that the effectiveness of the functioning of PhCo is also influenced by the risks of logistics in the field of FEA